PENGENALAN DAN PENGEMBANGAN E-MODUL BAGI GURU- GURU SMAN 2 PADANG PANJANG - guspatni guspatni (Fakultas MIPA Universitas Negeri Padang, 2019)
This society service was done in regard to request from teachers in SMAN 2 Padang Panjang who wanted to be given training on the development of e-module as one of innovative instructional materials that can be used in learning process and serves as a credit for career promotion as well. The designed e-module consisted of module components and was based on scientific approach suggested by curriculum 2013. E-module had interactive features with pictures, videos, hyperlinks, pop-up windows and interactive quizzes embedded. Data obtained from questionnaire and observation during training show that teachers were interested in e-module and wanted to use it in learning process. Teachers perceived e-module as instructional material having attractive design and one that could ease students to learn anywhere and anytime.